2017
DOI: 10.1136/bmjopen-2016-015568
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a lumbopelvic monitor and feedback device to change postural behaviour: a protocol for the ELF cluster randomised controlled trial

Abstract: IntroductionLow back pain (LBP) is the most common, costly and disabling musculoskeletal disorder worldwide, and is prevalent in healthcare workers. Posture is a modifiable risk factor for LBP shown to reduce the prevalence of LBP. Our feasibility research suggests that postural feedback might help healthcare workers avoid hazardous postures. The Effectiveness of Lumbopelvic Feedback (ELF) trial will investigate the extent to which postural monitor and feedback (PMF) can reduce exposure to hazardous posture as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 32 publications
0
3
0
1
Order By: Relevance
“…This trial was a participant-blinded, assessor-blinded, sham-controlled, parallel-group, stratified, cluster RCT. A detailed description of the trial can be found in the published protocol 14. The cluster RCT design was used to prevent treatment contamination between participants allocated to the intervention and sham groups 15.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This trial was a participant-blinded, assessor-blinded, sham-controlled, parallel-group, stratified, cluster RCT. A detailed description of the trial can be found in the published protocol 14. The cluster RCT design was used to prevent treatment contamination between participants allocated to the intervention and sham groups 15.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, the estimated sample size for the cluster RCT was a minimum of 108 participants, with 15 clusters (approximately 7 participants per cluster). A detailed description of sample size estimation is described in the published protocol 14…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, as discussed previously (see Section 3.1.1), the use of wearable motion capture instruments and systems may facilitate the detection of changes in biomechanical exposure due to their ability to collect data over full or several workdays and with high accuracy and precision. While traditional training using feedback often requires the presence of a trained instructor [253], some of the wearable motion capture systems have integrated automated feedback systems [85,87,99,104,105,257], which provide feedback of varies modalities such as audio, visual, or vibrotactile feedback (see Table 12 for an overview of various feedback characteristics), or a combination of several multimodalities.…”
Section: Work Technique Trainingmentioning
confidence: 99%
“…Em 2009, um sistema de vestuário que dá acesso à Internet foi desenvolvido pelo Laboratório de Tecnologia de Mídia do Instituto de Tecnologia de Massachusetts e marcou a chegada de uma nova era de têxteis eletrônicos (Lu et al, 2020). Um ensaio clínico randomizado realizado em 2017 na Nova Zelândia envolvendo trabalhadores que sofriam de lombalgia avaliou a eficácia de um dispositivo do tamanho de um pager capaz de detectar variações nos movimentos do tronco e sinalizar aos pacientes os padrões anormais da postura que prejudicam a coluna vertebral com vistas a prevenir os malefícios da dor na coluna vertebral (Ribeiro et al, 2017).…”
Section: Dispositivos Vestíveisunclassified